2005
DOI: 10.1158/1078-0432.ccr-04-1148
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-C Expression and Invasive Phenotype in Ovarian Carcinomas

Abstract: Purpose: To investigate the biological correlation between vascular endothelial growth factor (VEGF)-C expression and invasive phenotype in ovarian carcinomas. Experimental Design: Gene and protein expression levels of VEGF-C in 10 ovarian carcinoma cell lines were correlated with invasive activity of the cells. The correlation between immunohistochemical expression of VEGF-C and tumor aggressiveness in 73 ovarian carcinomas was also examined with respect to clinicopathologic features and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 35 publications
4
34
1
Order By: Relevance
“…In the tumor cells in both the primary cervix and the lymph node tumors, the localization pattern of CXCR4 showed positive membrane staining with cytoplasmic localization of the receptor, 37 and VEGFC showed a positive membrane stain. 38,39 uPAR staining was observed to be localized in the cytoplasm, but specific regions showed membrane staining consistent with literature reports. 40 Hdm2 stained positive in both the nucleus and cytoplasm.…”
Section: Immunolocalization Analysis Of Upregulated Genes Under Cyclisupporting
confidence: 91%
“…In the tumor cells in both the primary cervix and the lymph node tumors, the localization pattern of CXCR4 showed positive membrane staining with cytoplasmic localization of the receptor, 37 and VEGFC showed a positive membrane stain. 38,39 uPAR staining was observed to be localized in the cytoplasm, but specific regions showed membrane staining consistent with literature reports. 40 Hdm2 stained positive in both the nucleus and cytoplasm.…”
Section: Immunolocalization Analysis Of Upregulated Genes Under Cyclisupporting
confidence: 91%
“…On the other hand, VEGF-C was demonstrated to induce angiogenesis in the mouse cornea (66). Although VEGF-A and VEGF-C have been shown to play various roles in both angiogenesis and lymphangiogenesis in the animal models, there have been conflicting reports regarding the relationship between VEGF-A and VEGF-C and the LVD and MVD in human cancer tissues (37,41,45,47,55,(67)(68)(69)(70). The VEGF-C expression correlated positively with both the LVD and MVD in bladder (67), gastric (41) and ovarian (45) cancers, while no significant correlation ONCOLOGY REPORTS 23: 621-630, 2010 Table VII.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…[22][23][24][25][26] Some clinical studies have shown a correlation between tumor VEGF-C expression and lymph node metastasis. [27][28][29] Intrahepatic cholangiocarcinoma remains an unfortunate liver tumor with a high mortality rate, because many patients diagnosed with cholangiocarcinoma cannot be offered curative treatment. 30 One of the major hallmark of cholangiocarcinoma is its lymph node metastasis.…”
mentioning
confidence: 99%